DEVELOPING INSTRUCTIONAL VIDEO IN TEACHING WRITING FOR THE TENTH GRADERS - Sari, Dian Ayu Permata; Wardani, Happy Kusuma; Alimin, Alimin (STKIP PGRI Jombang, 2024)
For many years, educators have tried to find solutions to the students’ problem in writing performances by developing learning materials and media. This research aimed to develop an instructional video as technology-based media to teach writing for the tenth graders. As the developed product, the instructional video was expected to meet the needs of both students and the teacher while offering solutions for the challenges that arise in writing activities. The design of this research was Research and Development (R&D) by employing the ADDIE model that was carried out in five stages (Analysis, Design, Development, Implementation, and evaluation). In developing the product, some instruments were utilized to ease the data collection. Questionnaires and interviews were employed as needs analysis instruments, whereas an observation sheet was the instrument utilized in the implementation stage. In addition, the questionnaire was distributed in the last stage as the evaluation instrument to find out students’ opinions about the developed product. The result of this research was the instructional video to teach writing for the tenth graders which has been developed based on the results of needs analysis and revised based on the feedback from expert validators and teacher validator. Furthermore, in the evaluation stage, it revealed that the developed product gained good attention and engagement from the tenth graders of a private senior high school in Gresik.